Evaluation of tourism climate conditions at three stations of Noshahr, Ramsar and Rasht using the physiological equivalent temperature and average predicted polling index - Kakvan, Reza; Alijani, Bohloul; Saliqeh, Mohammad (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Provinces located on the southern shores of the Caspian Sea are one of the most important northern places in the country that have always attracted a great deal of tourists in different seasons of the year due to their various natural, human and historical attractions. Every year, they welcome different tourists. These beaches, while having attractive features for tourists, can also play a vital role in the sustainable development of the natural scenery and conservation area. One of the steps to reach sustainable development is tourism planning. The first step in this area is to assess the tourism climate in the country. In this study, in order to evaluate the conditions of the northern climate of Iran’s climate, the meteorological data of synoptic stations of Noshahr, Ramsar and Rasht have been used in a 30-year statistical period divided into three decades of age. The method used to assess the climate of comfort, the physiological equivalent temperature index, and the predicted mean of the survey. The results of this study show that the highest climatic conditions for spending leisure time and tourism activities in this region are two separate periods in the middle of spring (May and June) and the beginning of the fall season (October). The continuation of average heat stress from July to August and cold stress from different periods from November to the end of the winter season is a factor for tourism constraints during these months. For other months, they have relatively good weather conditions in terms of temperature and humidity in a little warm and slightly cool thermal condition. Also, changes over the decades indicate climate change and impact on thermal comfort.